2016
DOI: 10.3892/ol.2016.4392
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of M2-polarized macrophages in bladder cancer affects angiogenesis, tumor grade and invasiveness

Abstract: Abstract. Tumor-associated macrophages (TAMs) often assume an immunoregulatory M2 phenotype. Thus, the aim of the present study was to clarify the correlation of vascularity and TAMs, in particular the M2 phenotype in the stroma and tumor areas, with the clinical and pathological outcomes of patients with bladder cancer. The TAM counts and microvessel counts (MVCs) were determined immunohistochemically in 21 patients with bladder cancer. The number of infiltrating TAMs was measured using immunohistochemistry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…TAMs and their alternative activation together with cytokines and growth factors are trapped in tumor stroma and strongly contribute to the progression of OS [36]. Interestingly, in contrast to most other tumor types, M2 polarized macrophages reduce metastasis and improve survival in high-grade OS patients [25]. In vitro studies demonstrated that human macrophages can be stimulated by Mifamurtide to exert anti-tumor activity against OS cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAMs and their alternative activation together with cytokines and growth factors are trapped in tumor stroma and strongly contribute to the progression of OS [36]. Interestingly, in contrast to most other tumor types, M2 polarized macrophages reduce metastasis and improve survival in high-grade OS patients [25]. In vitro studies demonstrated that human macrophages can be stimulated by Mifamurtide to exert anti-tumor activity against OS cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to many other tumor types, M2 polarized macrophages, reduce metastasis and improve survival in high-grade OS patients. Macrophage polarization is also able to modulate iron sequestration and release [24][25][26][27][28].…”
Section: Research Papermentioning
confidence: 99%
“…Subsequent to adhesion to vascular endothelial cells, Mφ mature, begin phagocytosis, intracellular digestion, antigen presentation of Mφ and finally digest the crystal (24). However, M1 macrophages are pro-inflammatory, and M2 anti-inflammatory (25); M1s are associated with adipocytes and metabolic syndrome, whereas M2s are associated with organ restoration (26,27) and carcinogenesis (28). When crystals adhere to the renal tubular epithelium, M1-associated genes are highly expressed and promoted by adipocytes (29); in mice in which M2 macrophages are dysfunctional, M1 macrophages and kidney stone formation are increased (30).…”
Section: Discussionmentioning
confidence: 99%
“…Takeuchi et al (2016) to correlate the prevalence of M2 macrophages, angiogenesis, and clinic-pathological features in bladder cancer showed higher density of M2 macrophages in invasive bladder cancer in relation to non-muscle invasive cancers. Moreover, the higher the distribution of microvessels, the greater the degree of severity of cancer, and the predominance of M2 macrophage correlated to the amount of microvessels in bladder cancer and can have prognostic value for this type of cancer [45]. …”
Section: Angiogenesis and Lymphangiogenesismentioning
confidence: 99%
“…Thus, it was proposed that the mTOR pathway could be a critical element in the regulation of TAMs differentiation [45]. …”
Section: Angiogenesis and Lymphangiogenesismentioning
confidence: 99%